Up and running with AutoCAD 2012. - Gindis, Elliot (Academic Press, 2011)
Get "Up and Running" with AutoCAD using Gindis' combination of step-by-step instruction, examples, and insightful explanations. The emphasis from the beginning is on core concepts and practical application of AutoCAD in architecture, engineering and design. Equally useful in instructor-led classroom training or self-study, the book is written with the student in mind by a long-time AutoCAD user and instructor based on what works in the industry and the classroom Strips away complexities and reduces AutoCAD to easy-to-understand basic concepts Explains "why" something is done, not just "how": the theory behind each concept or command is discussed prior to engaging AutoCAD so the student has a clear idea of what they are attempting to do All basic commands are documented step-by-step: what the user types in and how AutoCAD responds is spelled out in discrete and clear steps with numerous screen shots Extensive supporting graphics (screen shots) and a summary with a self-test section and topic specific drawing exercises are included at the end of each chapter Also available in a 2D+3D version with 10 additional chapters covering 3D concepts. ISBN for the 2D+3D version is 978-012-387029-2